Anatomy of a health scare: education, income and the MMR controversy in the UK - Dan Anderberg; Arnaud Chevalier; Jonathan Wadsworth (Institute for the Study of Labor (IZA), 2008)
One theory for why there is a strong education gradient in health outcomes is that more educated individuals more quickly absorb new information about health technology. The MMR controversy in the UK provides a case where, for a brief period of time, some highly publicized research suggested that a particular multi-component vaccine, freely provided to young children, could have potentially serious side-effects. As the controversy set in, uptake of the MMR vaccine by more educated parents decreased significantly faster than that by less educated parents, turning a significant positive education gradient into a negative one. The fact that the initial information was subsequently overturned and the decline in uptake ceased suggests that our results are not driven by other unrelated trends. Somewhat puzzling, more educated parents also reduced their uptake of other non-controversial childhood vaccines. As an alternative to the MMR, parents may purchase single vaccines privately; the MMR is the only vaccine for which we observe a strong effect of income on uptake.
urn:nbn:de:101:1-20080711157
Keywords: H31; 610; Childhood vaccinations; health outcomes; education; Gesundheitsvorsorge; Bildungsniveau; Impfung; Kinder; Gesundheit; Großbritannien